Insulin injection knowledge, attitude, and practice of community nurses in a mountainous area of southwest Zhejiang in China: a multi-center cross-sectional study - Lan, Xuefen; Zheng, Simin; Ji, Xiaozhen; Chen, Ling; Zhou, Ling; Ye, Bin; Zhu, Qingqing; Zheng, Xiaojia; Lu, Shunfei (Frontiers in Endocrinology, 2025)
BackgroundSuboptimal insulin injection is widely used to treat Chinese patients with diabetes, with most patients being treated in primary care institutions. However, research on community nurses’ knowledge, attitude, and practice concerning insulin injection in less developed areas of China is extremely scarce.ObjectiveTo investigate the knowledge, attitude, and practice of community nurses concerning insulin injection in a mountainous area of southwest, Zhejiang, China.MethodsWe employed a cross-sectional study in 30 community healthcare service centers and 1911 randomly selected community nurses between 20th June to 20th July 2023. The Chinese insulin injection knowledge, attitude, and practice questionnaire was used to collect data. Descriptive, correlational, and multivariate linear regression analyses were performed by Stata version 15.0.ResultsIn total, 47.7% of nurses had poor insulin injection knowledge, while only 3.7% and 2.5% had poor levels of attitude and practice concerning insulin injection. Sex, location of the institution, working period, marital status, institutional manager, knowledge of the latest guidelines, and undertaking insulin injection training over the last year (all p<0.05) were all identified as independent predictors of insulin injection knowledge. Sex, working period, experience of delivering insulin education to patients, knowledge of the latest guidelines, and undertaking insulin injection training over the previous year (all p<0.05) were identified as independent predictors of insulin injection attitude. Location of the institution, sex, knowledge of the latest guidelines, and undertaking insulin injection training over the last year (all p<0.05) were all independent predictors of insulin injection practice.ConclusionCommunity nurses in this study (Southwest Zhejiang) had relatively good attitudes and practices towards insulin injection, although their specific knowledge was poor. Sex, location of the institution, working period, marital status, knowledge of the guidelines, experience in delivering education, and training experience exhibited significant relationships with the knowledge, attitude, and practice of insulin injection. Therefore, effective tailored, standardized guideline-based training should be recommended to improve the knowledge, attitude, and practice of community nurses regarding insulin injection, especially for married and younger male nurses.